Pre-Trial Settlement of Administrative Disputes in Lithuania: The Principal Legal Ideas and Values - Paškevičienė, Laura (Teisė, 2018)
[only abstract in English; full article, abstract in Lithuanian]In this article the author analyzes theoretical ideas and legal values serving a background to the regulation of the pre-trial resolution of administrative disputes as an area of law, seeking prerequisites for its integral conception, purpose and position in the Lithuanian legal system. The author is trying to investigate the sufficiency and adequacy of current leading scientific insights on guiding legal values and principles of the pre-trial administrative dispute resolution, due to the problematics of its dualistic (administrative executive and judicial) nature.
Keywords: none